2017
DOI: 10.1186/s12888-017-1261-y
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and delivery risk factors for developing postpartum depression in a sample of 3233 mothers from the Czech ELSPAC study

Abstract: BackgroundIn the postpartum period, certain groups of women are at a higher risk for developing depressive episodes. Several studies have described risk factors for developing postpartum depression (PPD). However, these studies have used limited numbers of participants, and therefore the estimated prevalence of PPD varies greatly.MethodsThe objective of this study is to identify the main risk factors for developing PPD by using data collected via the Czech version of the European Longitudinal Study of Pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
3
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 60 publications
8
72
3
8
Order By: Relevance
“…There are studies showing lower rate (1.4%) in South Korea, (5.4%) in the Netherlands and higher rate such as 12% in the Maldives, and 21.3% in Tabriz, Iran . Several protective factors from developing PPD described in the literature including social support from family members and friends . Generally, traditional support during postpartum period comes from other family members (grandparents, relatives) in Turkish family, and in this study, majority of women stated they had support during postpartum period from at least one of their relatives.…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…There are studies showing lower rate (1.4%) in South Korea, (5.4%) in the Netherlands and higher rate such as 12% in the Maldives, and 21.3% in Tabriz, Iran . Several protective factors from developing PPD described in the literature including social support from family members and friends . Generally, traditional support during postpartum period comes from other family members (grandparents, relatives) in Turkish family, and in this study, majority of women stated they had support during postpartum period from at least one of their relatives.…”
Section: Discussionmentioning
confidence: 52%
“…15 Several protective factors from developing PPD described in the literature including social support from family members and friends. 4,24 Generally, traditional support during postpartum period comes from other family members (grandparents, relatives) in Turkish family, 8 The rate of cesarean section in the sample was 37.2%, which is lower than the mean rate in Turkey overall. The Organization of Economic Co-operation and Development has reported that Turkey's rate of cesarean section (53.1%) is the highest worldwide, 26 which is significantly higher than the acceptable rate (15%) of the World Health Organization.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations